STATEOWNED ENTERPRISE AND PUBLIC SERVICE OBLIGATION IN THE SECTOR OF OIL AND GAS - Muhammad Insa Ansari (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2017)
AbstractThe 1945 Constitution of the Republic of Indonesia regulates natural recources in its particular article. Then, the Energy Law and the Oil and Gas Law regulate the state’s control of oil and natural gas. In the sectoral regulations of oil and gas, there is a public service obligation (PSO) which must be assumed by the Government and State Owned Enterprises (SOE). Meanwhile, in the SOE Law introduced entity Perum and Persero. Where in Perum entities carrying out public service, while the Persero entity to assume the role for profit. But in practice found a PSO on the oil and gas sector carried by state-run entities Persero. IntisariDalam Undang-Undang Dasar Negara Republik Indonesia 1945 diatur penguasaan negara terhadap sumber daya alam. Kemudian UU Enegi dan UU Minyak dan Gas Bumi mengatur penguasaan negara terhadap minyak dan gas bumi. Dalam pengaturan sektoral di bidang tersebut juga mengatur kewajiban pelayanan umum yang harus diemban oleh pemerintah dan BUMN. Sementara itu dalam UU BUMN diperkenalkan  entitas Perusahaan Umum (Perum) dan Perseroan Terbatas (Persero). Dimana entitas Perum mengemban peran pelayanan umum (public service), sementara entitas Persero mengemban peran mencari keuntungan (profit oriented). Namun dalam praktek ditemukan kewajiban pelayanan umum pada sektor minyak dan gas bumi diemban oleh BUMN dengan entitas Persero.